Luisia yunnanensis (Orchidaceae; Epidendroideae), a new species from China: evidence from morphology and DNA analyses - Huang, Jie; Yu, Yu Yun; Chen, Gui-Zhen; Liao, Xing-Yu; Liu, Zhong-Jian; Peng, Dong-Hui (Phytotaxa, 2020)
Based on morphological and molecular evidence, Luisia yunnanensis (Epidendroideae, Orchidaceae), a new species from Yunnan, China, is described and illustrated. A detailed comparison between the newly discovered orchid and other members of Luisia is presented. Molecular analysis of nrITS and plastid DNA (matK, rbcL) sequence data show that L. yunnanensis is sister to L. filiformis with strong support.